Are Fatwas Visible on New Media? Dissemination of the Fatwas of the Indonesian Ulama Council on Instagram - Mualimin; Oztunc, Mustafa; Isman, Aytekin; Yunaldi, Ari; Saliro, Sri Sudono; Widodo, Anton; Aziz, Nana Abdul (El-Mashlahah, 2025)
The emergence of new media has a considerable impact on religion, including religious authorities’ dissemination of religious information and fatwas. This article explored on how exposure to new media affects the dissemination of religious information. Specifically, this article aimed to analyze the dissemination of the Indonesian Ulama Council (MUI) fatwa on Instagram. The article is a normative legal study of contemporary Islamic laws. Data has been collected by observing posts by the Indonesian Ulama Council (MUI) on Instagram from 2017 to 2023. The data was analyzed using content analysis methods with a socio-legal approach. This approach highlighted how fatwas work as legal norms disseminated, accepted, and interpreted by society on social media. This study found that from 2017 to 2023, there were 1093 content posted on the official Instagram account of the Indonesian Ulama Council (MUI). However, of all the content, only 9.6% (105 posts) were related to fatwa. This study also found that the posted of fatwa content tends to be response-based rather than indeed programmed in a conceptualized and patterned way to build Islamic law literacy in the community. Based on these findings, it concluded that Instagram has yet to be used as a tool to build public fatwa literacy and a medium for disseminating Islamic law issued by the Indonesian Ulama Council has. The findings have significance as an academic reference for the Indonesian Ulama Council (MUI) and religious authority institutions in Indonesia in designing religious fatwa dissemination policies in response to the exposure of new media.